Antioxidant Activities and Î±-glucosidase Inhibition of Gayo Arabica Coffee Skin (Coffea arabica L) - Baharuddin Yusuf Habiby Harahap; Hasim Hasim; Didah Nur Faridah (Current Biochemistry, 2021)
This research objectives to determine antioxidant activities and inhibition of Î±-glucosidase 96 % ethanol extract of gayo arabica coffee skin, n-hexane fraction, ethyl acetate fraction, and water fraction. Gayo arabica coffee skin was extracted by ethanol using maceration and fractionation using n-hexane, ethyl acetate, and water. Quercetin and Gallic acid were used as standard to found total flavonoids and phenolics. Test of antioxidant activity using the DPPH method. After being tested the inhibition of the Î±-glucosidase IC50 ethanol extract, the n-hexane fraction, ethyl acetate fraction, and water fractions. The total flavonoids of 96% ethanol extract, n-hexane fraction, ethyl acetate, and water fraction respectively are 76.74, 99.07, 73.55, 50.24 mg QE/g extract . Total phenolics of 96% ethanol extract, n-hexane fraction, ethyl acetate, and water fraction respectively are respectively 211.85, 136.67, 145.19, 127.41 mg GAE/ g extract. Antioxidants activity of ethanol extract, n-hexane fraction, ethyl acetate fraction, and water fraction are IC50 12.03 ppm, 36.08 ppm, 30.27 ppm, 11.62 ppm. Inhibition activity Î±-glucosidase enzyme respectively are 588.85 ppm, 341.81 ppm, 591.61 ppm, and 798.78 ppm. These showed that the ethanol extract and water fraction are the best in antioxidants and the ethanol extract and ethyl acetate fraction are the best in inhibiting the Î±-glucosidase enzyme. These results indicate that gayo arabica coffee skin extract has the potential to be developed as an antidiabetic compound. Keywords: Antidiabetic, Antioxidant, flavonoids, phenolics, Î±-glucosidase